Effect of Addition of Pandan Leaf Infusa (Pandanus amaryllifous, R) on Carcass Weight, Carcass Percentage and Abdominal Fat of Broilers: Pengaruh Penambahan Infusa Daun Pandan (Pandanus amaryllifous, R) terhadap Bobot Karkas, Persentase Karkas dan Lemak Abdominal Broiler - Sikumbang, Chairani Mukherji; Nilawati, Nilawati; Malvin, Toni; Fati, Nelzi (Buletin Peternakan Tropis, 2024)
Many natural components are currently being looked for as substitute feed additives in broiler feed and drinking water to increase the effectiveness and quality of broiler production. Pandan leaves are one possible herbal component. The study's goal was to determine the optimal pandan infusion dosage for broiler carcasses, abdominal fat deposition. In this study, one hundred broiler aged one day were divided into 4 treatments and 5 replicates using a completely randomized design (CRD). The trial lasted four weeks in the Payakumbuh State Agricultural Polytechnic production laboratory's broiler stage cage.  Twenty broilers per treatmnets were given pandan leaf infusa to drinking water. The four tretamnets were as follows:  no additon of pandan infusion (A0), 1% addition (A1), 2% addition (A2) and; 3% addition (A3). The findings demonstrated that the research variables were not significantly impacted (P̃ > 0.05) by the addition of pandan leaf infusa to drinking water. The percentage of carcass ranged from 66.52% to 71.56%, and the percentage of abdominal fat ranged from 0.92% to 0.77%. These findings lead to the conclusion that adding up to 3% of leaf infusion to drinking water did not improved carcass and abdominal fat deposition.